Network pharmacological investigation and experimental verification of the peel of Zea mays L. regulating metabolic reprogramming in the treatment of diabetic nephropathy - Wang, Andong; Yang, Yuru; He, Yaonan; Chen, Guangtong; Ling, Bai; Cheng, Xiaotian (Frontiers in Endocrinology, 2025)
BackgroundZea mays L. is one of the most significant genes in the Gramineae family, and the peel of Zea mays L. (YMP), an unproven folk remedy for diabetes, has not been well studied. Diabetic nephropathy (DN) is one of the most well-known and dangerous microvascular effects of diabetes mellitus. The effects and mechanisms of YMP on metabolic reprogramming are largely unknown.MethodsThe components of YMP were systematically identified using UPLC-Q-TOF-MS/MS. A network pharmacology study between DN and significant components was then carried out. The pharmacological trials of YMP were evaluated in mice with diabetes. In vitro measurements were made of the biochemical activity, anti-inflammatory, and antioxidant properties. Moreover, UHPLC-LTQ-Orbitrap MS was used to do investigations on the metabolomics of serum and urine. Ultimately, transcriptomics analysis was utilized to clarify the complex processes by which the transcription factor influences DN.Results43 components were systematically identified from YMP. It was found by network pharmacology analysis that signal transduction, namely metabolic disruption, involved pathways with a high degree of engagement. Experimental verification showed that YMP administration increased glomerular hypertrophy, collagenous tissue proliferation, urine microalbumin/creatinine ratio, inflammatory response remission, and oxidative stress promotion in vivo. Treatment with YMP may affect the pathways that are involved in the metabolism of amino acids and energy, as well as reverse metabolite abnormalities. YMP has the ability to restore the levels of metabolites like Gluconolactone, D-Ribulose 5-phosphate, Xylulose 5-phosphate, L-Alanine, L-Aspartic acid, Glutamic acid, Citrulline, L-Arginine, L-Leucine, L-Valine, L-Isoleucine, and so on. Metabolic reprogramming of energy metabolism was demonstrated. By transcriptomics, when STZ is administered, the GPI, GAPDH, G6PC, HK2, HK1, and HK3 genes associated with glycolysis/gluconeogenesis were significantly elevated from the model groups. However, the pentose phosphate pathway-related genes G6PD, PGLS, RPE, TALDO1, and HXLB significantly elevated when YMP was administered.ConclusionsThis study was the first to show that YMP corrected disruptions in the pentose phosphate pathway and amino acid metabolism, alleviated diabetes-induced pathological changes in the kidneys of diabetic mice, and had a regulating effect on the liver glycolipid metabolism. By investigating the novel pharmacological effect of traditional Chinese medicine and encouraging in-depth study and development, this work may offer a new experimental foundation and theoretical direction for the sensible application of YMP on DN.